Morphometry of Calcaneus in Tiger (Panthera tigris) - Pandey, Yogita (Indian Journal of Veterinary Anatomy, 2020)
The present investigation was carried out on calcaneus of three adult tigers. The calcaneus (fibular tarsal) was the longest as well as largest bone among the tarsal bones. The body of the calcaneus was compressed from side to side and directed upwards and backwards, its length was 8.73±0.075 cm laterally and 6.40±0.048 cm medially. The tuber calcanei (circumference: 8.43±0.085 cm) was traversed dorsally by latero-medial groove. Lateral process on free end of tuber calcis was not well marked, whereas the medial process of tuber calcis was well defined and in the form of summit. The medial surface of the body was concave and the lateral surface was convex. On the distal end of fibular tarsal a large slightly concave facet was present measuring 3.13±0.048 cm in length and 2.20±0.041 cm in width, which was quarter circular in shape and articulated with central and tibial tarsal. The facet was limited by a sharp boundary except caudally where it was rough.